Subjective Norms of Health Students Related to Parent's Social Control on Intention to Stop Smoking - Ahsanu Bil Husna; Ira Nurmala; Erdi Istiaji; Erwin Nur Rif'ah (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Smoking among students is a significant global issue. Health students, expected to be knowledgeable about smoking dangers and serve as role models, are found to engage in smoking behavior, which is concerning. This study aimed to analyze health students' perceptions regarding parental social control and their intention to quit smoking using the Theory of Planned Behaviour, specifically focusing on the role of subjective norms. The study used a descriptive qualitative approach with a phenomenological methodology involving in-depth interviews and observations. The research was conducted in Jember Regency with five primary informants, health students at the University of Jember, and key informants who were close friends and parents of primary informants. Data processing used the interactive data analysis model proposed by Miles and Huberman, involving three steps: data reduction, data presentation, and conclusion drawing. The study found that health students who smoke positively perceived their parents' opinions and social support regarding smoking cessation behavior. They viewed their parents' efforts to prevent them from smoking as beneficial and effective in influencing their behavior. health students who smoke acknowledged that the social control exerted by their parents was crucial in helping them overcome their smoking habits. Most health students who smoke expressed a strong intention to quit smoking, indicating a willingness to change their behavior in response to the support they received from their parents. The study suggests that parents should set a good example and communicate effectively to influence adolescent smoking behavior. Health students and health offices can also support this effort through smoking cessation activities and education.